The Influence Of Social Media Marketing And User Generated Content On Purchase Intention Of Local Product Y.O.U Among Generation Z (A Case Study At Dehasen University) - Ridha Tri Desita; Tito Irwanto; Ida Ayu Made Er Meytha Gayatri (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to examine the influence of Social Media Marketing (SMM) and User Generated Content (UGC) on Purchase Intention of the local cosmetic brand Y.O.U among Generation Z students at Dehasen University. The research employed a quantitative approach using a purposive sampling technique with 55 respondents who are active Generation Z students. Data were collected through questionnaires using a Likert scale and analyzed using validity and reliability tests, multiple linear regression analysis, t-test, F-test, and the coefficient of determination (R²) with SPSS version 22. The results indicate that Social Media Marketing has no significant effect on Purchase Intention (significance value 0.103 > 0.05), while User Generated Content has a positive and significant effect (significance value 0.000 < 0.05). Simultaneously, both variables have a significant influence on Purchase Intention with an R² value of 0.872, meaning that 87.2% of the variation in purchase intention can be explained by SMM and UGC. These findings highlight that user-generated content plays a dominant role in shaping Generation Z’s purchase intention toward Y.O.U products, while social media marketing activities need to be further optimized to effectively influence consumers’ buying decisions.